1999
DOI: 10.1103/physrevb.59.15910
|View full text |Cite
|
Sign up to set email alerts
|

Conductance of a finite missing hydrogen atomic line on Si(001)-(2×1)-H

Abstract: We present the results of a calculation of zero-temperature elastic conductance through a finite ''atomic wire'' between Au pads, all supported by a Si͑001͒-͑2ϫ1͒-H surface. The atomic wire consists of a line of dangling bonds which can be fabricated by removing hydrogen atoms by applying voltage pulses to a scanning tunneling microscopy ͑STM͒ tip along one side of a row of H-passivated silicon dimers. Two different line configurations, without and with Peierls distortion, have been considered. We find that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 46 publications
(48 reference statements)
4
65
0
Order By: Relevance
“…For example, it has been shown both experimentally and theoretically that a Peierls-like transition also occurs in dangling-bond (DB) lines fabricated on the H-passivated Si(001) surface [83][84][85] . More recently, it has been shown theoretically that the injection of a static charge in the bands around the band-gap leads to a distortion of the atomic positions along the line 86 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown both experimentally and theoretically that a Peierls-like transition also occurs in dangling-bond (DB) lines fabricated on the H-passivated Si(001) surface [83][84][85] . More recently, it has been shown theoretically that the injection of a static charge in the bands around the band-gap leads to a distortion of the atomic positions along the line 86 .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In the context of molecular electronics, hydrogenated silicon surfaces are also used for atomic-scale patterning of reactive sites 5,6 or conducting lines. [7][8][9][10][11][12] As a result, the atomic structures of hydrogenated Si͑100͒ surfaces have attracted much attention over the past few years. [13][14][15] The adsorption of hydrogen atoms on the Si͑100͒ surface can lead to different surface reconstructions, depending on the surface temperature during the hydrogen adsorption-desorption cycles.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced atom manipulation ability of scanning probes have permitted the creation of quasi 1-D surface states with extraordinary properties. 18,19,[21][22][23][24][25][26] Experimental 18 and theoretical studies 17,21,22,24,25,27 have shown that in the limit of one-atom wide dangling-bond wires, 1-D correlations are very strong and instabilities set in creating electronic gaps in the wire's electronic structure. As recently shown, this has detrimental consequences in the wires' electron-transport properties, 28 reducing the possibilities of dangling-bond wires as alternative interconnects to free-standing 13,14 or embedded 16 nanowires.…”
mentioning
confidence: 99%
“…As a remedy for this limitation, Weber et al 16 have recently embedded nanowires on a silicon surface by selectively doping using scanning-probe technology. Previously, an alternative but related approach has been proposed [17][18][19] in which surface electronic states were engineered, taking advantage of the very local nature of silicon bonds. By creating dangling-bond nanowires on silicon surfaces, surface electronic states can be precisely tuned.…”
mentioning
confidence: 99%